Superhydrophobic coatings on Portland cement concrete surfaces. (15th June 2017) - Arabzadeh, Ali; Ceylan, Halil; Kim, Sunghwan; Gopalakrishnan, Kasthurirangan; Sassani, Alireza; Sundararajan, Sriram; Taylor, Peter C.
Highlights: Portland cement concrete (PCC) surfaces were coated with low surface energy materials. Layer-by-layer (LBL) deposition technique was utilized for coating the PCC substrates. The coated PCC substrates reached high levels of hydrophobicity (water-repellency). Effect of concrete surface texture was studied on the skid resistance of coated concrete. Turf drag surface texture greatly enhanced the skid resistance of superhydrophobic PCC. Abstract: The objective of this study was to synthesize, characterize and evaluate the nanomaterials-based superhydrophobic (super water-repellent) coatings on Portland cement concrete (PCC) surfaces. These coatings are synthesized with nanomaterials such as polytetrafluoroethylene (PTFE), polyether ether ketone (PEEK) and silanized diatomaceous earth (DE). Using layer-by-layer (LBL) deposition technique, each coating type was deposited at four different spray durations. The water-repellency of the coated surfaces were characterized by measuring static water contact angles (WCAs). These measurements were evaluated through a statistical design-based experimental test program which revealed that the spray duration and coating type are significant variables. A skid-resistant coating composed of PTFE and PEEK was utilized to evaluate the impact of superhydrophobic coatings on pavement skid resistance.